Does company size and profitability affect corporate social responsibility disclosure? - Syahierah, Rukaanisy; Larasati, Ashilla (Asian Journal of Islamic Management (AJIM), 2020)
Purpose: This research is aimed to analyze whether disclosure of corporate social responsibility (CSR) of sharia bank in Indonesia is influenced by some factors. Methodology: This research used the data from Islamic Social Reporting (ISR) index. ISR was evaluated based on content analysis; that is by analyzing annual report of 11 sharia banks. Findings: Multiple regressions showed that company size significantly affected the level of disclosure of CSR but it was the contrary for profitability. Originality/contributions: This is the first study to used 11 sharia banks in Indonesia during the period of 2010-2013.